An analysis of the effectiveness of the budgetary control mechanisms on value addition to the hotel industry: A case study of The Kingdom at Victoria Falls Hotel - Kwaru, Timothy (2017)
The Kingdom at Victoria Falls Hotel was suffering from adverse variances in its budgeted fixed and variable costs and EBITDA for the years between 2013 and 2015 in failure to meet the targets. These adverse budget variances were eroding the shareholders’ wealth. The existence and primary mandate for any business establishment is to maximize the shareholders’ wealth creation through adding value through effective and efficient use of the available scarce resources. Earlier scholars studies dwelled much on budgetary implementation and how it affects organizational performance, although these studies tried to address the correlation between budgetary implementation tools on organizational performance, they did not conclusively address how effective budgetary control mechanisms are, on value addition. Therefore, to address the anomaly the researcher sought to fill this gap by analyzing the effectiveness of budgetary control mechanisms on value addition to The Kingdom at Victoria Falls Hotel. The descriptive research approach was used to test both the theoretical and empirical reviews done. Triangulation was used for justification of research methodology used for data collection; and data presentation. Validity and reliability was improved by collecting closed-ended questionnaires and structured interviews with TKVFH eighteen participants out of twenty which were targeted. Data was presented and analyzed, the research outcomes and the results obtained in the sample research held vital implications on the management for overcoming the factors affecting budgetary control systems and strategies that can be used. Graphical presentation has been employed to communicate the processed data which is of quality. A positive relationship was discovered exists between budgetary control mechanisms and both the key performance indicators and value addition at TKVFH.